The use of beta-D-glucanase as a substitute for Novozyme 234 in immunofluorescence and protoplasting - M Katherine Jung; Yulia Ovechkina; Natalie Prigozhina; C Elizabeth Oakley; Berl R Oakley (Fungal Genetics Reports, 2000)
Novozym 234 has been used for many years to prepare protoplasts of Aspergillus nidulans and other fungi for transformation. It has also been very useful in immunofluorescence studies for partially digesting walls of fixed hyphae or germlings to allow antibodies to penetrate into the cytoplasm. In recent years, the availability of Novozym 234 has become problematic, and we have searched for combinations of available enzymes that are suitable for protoplasting and immunofluorescence studies in A. nidulans.